High-temperature-resistant and high-humidity-resistant anti-static base coating liquid, anti-static coating and preparation method thereof

By optimizing the components and cross-linking reaction of the PEDOT:PSS antistatic liquid, an antistatic layer with a high cross-linking density is formed, which solves the problem of conductivity attenuation of PEDOT:PSS in high temperature and high humidity environments, and improves the stability and conductivity of the antistatic layer, making it suitable for flexible electronic devices.

CN120607857APending Publication Date: 2025-09-09SUZHOU SHIHUA NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510603018.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

The existing PEDOT:PSS materials experience conductivity decay and reduced surface resistance stability under long-term hot and humid environments, and domestic high-end products have insufficient performance, making it difficult to fully replace traditional solutions in the antistatic layer of optical film materials.

Method used

PEDOT/PSS antistatic liquid is used with thermosetting waterborne polyurethane, multifunctional aziridine crosslinker, epoxy silane coupling agent and other components to form a three-dimensional network with high crosslinking density through crosslinking reaction. Combined with high-boiling point polar solvents and surfactants, the dispersion and adhesion properties of PEDOT:PSS are optimized.

Benefits of technology

In high temperature and high humidity environments, the antistatic layer maintains excellent conductivity and adhesion properties, extends its service life, improves the stability and conductivity of PEDOT:PSS, and adapts to the needs of flexible electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and particularly discloses a high-temperature-resistant and high-humidity-resistant antistatic prime coat liquid, an antistatic coating and a preparation method thereof. The preparation method comprises the following steps: taking a poly (3, 4-ethylenedioxythiophene)-polystyrolsulfon acid (PEDOT: PSS) antistatic primer solution as a main agent, and adding thermosetting waterborne polyurethane, a doped organic solvent, a pH regulator, a surfactant, a silane coupling agent, a polyfunctional group aziridine cross-linking agent and a diluent formed by blending water and isopropanol to prepare the antistatic primer solution; and coating the PET base material through an anilox roller to obtain the PEDOT: PSS antistatic coating. According to the invention, the high temperature resistance, high humidity resistance, friction resistance and solvent resistance of the PEDOT: PSS antistatic coating are enhanced, and the problem that the antistatic performance of the traditional PEDOT: PSS antistatic coating is reduced after common wiping and solvent wiping under high temperature and high humidity conditions is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, in particular to a high-temperature and high-humidity resistant antistatic primer, an antistatic coating and a preparation method thereof. Background Art

[0002] In the field of optical film materials, the core demand for antistatic layers stems from the dual pursuit of optical performance and reliability in display devices (such as LCD, OLED) and flexible electronic devices. Since static electricity accumulation can easily lead to problems such as dust adsorption and component breakdown, the antistatic layer needs to maintain high transparency (≥85% visible light transmittance) while precisely controlling the surface resistance (10 6 ~10 9 Ω), and has the characteristics of resistance to temperature and humidity changes, low haze (<1%), resistance to chemical solvent cleaning and substrate compatibility.

[0003] While traditional metal oxides (such as ITO) offer excellent conductivity, their brittleness makes them difficult to adapt to the trend toward flexibility. Carbon-based or metal nanowire materials, on the other hand, face bottlenecks such as uneven dispersion and high costs. Against this backdrop, PEDOT:PSS, a water-soluble conductive polymer, stands out. The combination of PEDOT conductive chains and PSS dispersants in its molecular structure allows for the formation of transparent conductive films on substrates such as PET through solution processing (e.g., coating and printing). Combined with its flexibility, it is particularly suitable for emerging applications such as foldable screens.

[0004] However, the material's conductivity degradation in long-term hot and humid environments, reduced surface resistance stability after prolonged friction or chemical solvent cleaning, and insufficient performance of domestic high-end products continue to hinder its full replacement of traditional solutions. Currently, international companies have achieved some high-end applications through doping and modification, while the domestic industry chain is accelerating technological research to overcome stability and cost bottlenecks and promote the large-scale application of PEDOT:PSS in antistatic layers of optical films.

[0005] In order to solve the above problems, the present invention provides a high-temperature and high-humidity resistant antistatic primer, an antistatic coating and a preparation method thereof. Summary of the Invention

[0006] The object of the present invention is to provide a high temperature and high humidity resistant antistatic primer, an antistatic coating and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A high temperature and high humidity resistant antistatic primer liquid comprising the following substances:

[0009] Component A: PEDOT / PSS antistatic liquid with a solid content of 1.5-2.5%;

[0010] Component B: thermosetting waterborne polyurethane with a solid content of 33-38%;

[0011] Component C: doping organic solvent;

[0012] Component D: pH regulator;

[0013] Component E: surfactant;

[0014] Component F: silane coupling agent;

[0015] Component G: a multifunctional aziridine crosslinker with a solid content of 9%-11%;

[0016] Component H: a mixed solution of water and isopropyl alcohol.

[0017] More optimally, the mass of component B is 15-30% of the mass of component A, the mass of component C is 0.5-10% of the mass of component A, the mass of component D is 1-3% of the mass of component A, the mass of component E is 0.1-0.5% of the mass of component A, the mass of component F is 0.1-0.5% of the mass of component A, the mass of component G is 3-7% of the mass of component A, and the mass of component H is 9-15 times the mass of component A.

[0018] More optimally, the mass ratio of PEDOT to PSS in the PEDOT / PSS antistatic liquid is 1:2.5-1:3.

[0019] More optimally, the thermosetting waterborne polyurethane is a thermosetting waterborne polyurethane containing hydroxyl groups and carboxyl groups.

[0020] More optimally, the doping organic solvent is a high-boiling-point polar solvent, including but not limited to at least one of ethylene glycol, dimethyl sulfoxide (DMSO), sorbitol, and N-methylpyrrolidone.

[0021] More optimally, the pH regulator is an amine compound, including but not limited to one of N,N-dimethylethanolamine, triethanolamine, and tert-butyldiethanolamine.

[0022] More optimally, the surfactant is specifically an acetylenic diol nonionic surfactant.

[0023] More optimally, the silane coupling agent is an epoxy silane coupling agent, including but not limited to γ-glycidyloxypropyltrimethoxysilane.

[0024] More optimally, the multifunctional aziridine crosslinker is a trifunctional aziridine, including but not limited to one of trimethylolpropane-tris[3-(2-methylaziridinyl)propionate] and pentaerythritol tris(3-aziridinyl)propionate.

[0025] More optimally, in the H component, the mixed solution of water and isopropanol is a mixed solution of water and isopropanol in a mass ratio of 1:1 to 1:2.5.

[0026] The present invention provides a high-temperature and high-humidity resistant antistatic coating, which is prepared from any one of the above-mentioned high-temperature and high-humidity resistant antistatic primers. The thickness of the antistatic coating is 0.05 to 0.1 μm.

[0027] The present invention also provides a method for preparing a high-temperature and high-humidity resistant antistatic coating, which is used to prepare the above-mentioned high-temperature and high-humidity resistant antistatic coating, comprising the following steps:

[0028] S1. Mix the water and isopropyl alcohol in component H and stir for 5 minutes, then let it stand for 5 minutes. Then, add components A, B, C, D, E, and F to component H in sequence and disperse them for 20-30 minutes. Finally, add component G and disperse for 5 minutes to obtain an antistatic primer.

[0029] S2, coating the obtained antistatic primer on a PET substrate, controlling the dry coating thickness to be 0.05-0.1 μm, and curing at 120° C. for 1 minute to obtain a stable high-temperature and solvent-resistant antistatic layer.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The present invention achieves synergistic effects by rationally combining the components in the antistatic primer, so that the antistatic layer prepared by the antistatic primer of the present invention still has excellent conductive properties and strong adhesion properties under high temperature and humidity, multiple friction and solvent action, thereby obtaining the optimal formula.

[0032] (2) During the thermal curing process of the antistatic layer prepared by the present invention, under the action of high temperature, multiple aziridine groups react with the hydroxyl and carboxyl groups in the thermosetting waterborne polyurethane to undergo nucleophilic reactions, forming stable covalent bonds while constructing a three-dimensional cross-linked network with high cross-linking density and hard segment aggregation. The cross-linked network with high cross-linking density reduces the free volume, closes the microscopic pores, and effectively hinders the penetration of organic solvent molecules and the diffusion path of water molecules; the aggregated hard segments significantly improve the friction resistance of the PEDOT:PSS antistatic coating.

[0033] (3) The high-boiling-point polar organic solvent used in the present invention weakens the electrostatic interaction between PSS and PEDOT, promotes the migration or partial removal of PSS, thereby exposing more conductive PEDOT chains. The solvent molecules are inserted between the PEDOT chains, reducing the interchain steric hindrance, promoting the extension and orderly stacking of the PEDOT molecular chains, and forming a more continuous conductive path, so that the antistatic protective liquid still has a high conductivity even with a lower PEDOT:PSS addition amount.

[0034] (4) The epoxy silane coupling agent used in the present invention can form chemical bonds or hydrogen bonds with polar groups (such as sulfonic acid groups) in PEDOT:PSS through its epoxy group, and at the same time, the silane end reacts with the PET substrate, thereby reducing the negative impact of the hydrophilicity of PSS on the stability of the material. In a high temperature and high humidity environment, it inhibits the decrease in conductivity caused by moisture penetration, effectively extending the service life of the antistatic coating.

[0035] (5) The surfactant used in the present invention reduces the surface tension or interfacial tension of the substrate, allowing the aqueous substance to spread more easily on the surface of the substrate, thereby further promoting the dispersion of the solution on the surface of the object and effectively improving the film-forming performance of the antistatic liquid. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0037] Table 1 shows the information related to the antistatic liquid, thermosetting waterborne polyurethane, multifunctional aziridine crosslinking agent, and surfactant used in the examples of the present invention.

[0038] Table 1: Models and purchasing channels of each component used in the examples

[0039]

[0040]

[0041] The present invention verifies the effect of the antistatic layer prepared by several embodiments and comparative examples.

[0042] Example 1:

[0043] The components of the antistatic liquid include: 1 kg of component A; 250 g of component B; 50 g of N-methylpyrrolidone; 20 g of N, N-dimethylethanolamine; 3 g of component E; 2 g of component F; 50 g of component G; and 6 kg each of water and isopropyl alcohol.

[0044] The method for preparing an antistatic layer resistant to high temperature and high humidity comprises the following steps:

[0045] 1) Mix the water and isopropyl alcohol in component H and stir for 5 minutes, then let it stand for 5 minutes. Then, add components A, B, C, D, E, and F to component H in sequence and disperse for 30 minutes. Finally, add component G and disperse for 5 minutes to obtain an antistatic primer.

[0046] 2) The antistatic primer prepared in step 1) was coated on a PET substrate, the dry coating thickness was controlled to be 0.08 μm, and the coating was cured at 120° C. for 1 minute to obtain a stable high-temperature and solvent-resistant antistatic layer.

[0047] Example 2:

[0048] The formula of the antistatic liquid includes: 1 kg of component A; 300 g of component B; 23 g of N-methylpyrrolidone; 18 g of tert-butyldiethanolamine; 2.5 g of component E; 2.5 g of component F; 70 g of component G; and 4 kg of water and 10 kg of isopropyl alcohol.

[0049] The method for preparing an antistatic layer resistant to high temperature and high humidity comprises the following steps:

[0050] 1) Mix the water and isopropyl alcohol in component H and stir for 5 minutes, then let it stand for 5 minutes. Then, add components A, B, C, D, E, and F to component H in sequence and disperse for 30 minutes. Finally, add component G and disperse for 5 minutes to obtain an antistatic primer.

[0051] 2) The antistatic primer prepared in step 1) was coated on a PET substrate, the dry coating thickness was controlled to be 0.05 μm, and the coating was cured at 120° C. for 1 minute to obtain a stable high-temperature and solvent-resistant antistatic layer.

[0052] Example 3:

[0053] The formula of the antistatic liquid includes: 1 kg of component A; 150 g of component B; 80 g of N-methylpyrrolidone in component C; 28 g of N, N-dimethylethanolamine in component D; 2 g of component E; 3 g of component F; 30 g of component G; and 3 kg of water and 6 kg of isopropyl alcohol in component H.

[0054] The method for preparing an antistatic layer resistant to high temperature and high humidity comprises the following steps:

[0055] 1) Mix the water and isopropyl alcohol in component H and stir for 5 minutes, then let it stand for 5 minutes. Then, add components A, B, C, D, E, and F to component H in sequence and disperse for 30 minutes. Finally, add component G and disperse for 5 minutes to obtain an antistatic primer.

[0056] 2) The antistatic primer prepared in step 1) was coated on a PET substrate, the dry coating thickness was controlled to be 0.1 μm, and the coating was cured at 120° C. for 1 minute to obtain a stable high temperature and high humidity resistant antistatic layer.

[0057] Comparative Example 1:

[0058] The same formula and steps as those in Example 1 were used to prepare an antistatic layer resistant to high temperature and high humidity, except that the amount of component B was 100 g.

[0059] Comparative Example 2:

[0060] The same formula and steps as those in Example 1 were used to prepare an antistatic layer resistant to high temperature and high humidity, except that the amount of component B was 400 g.

[0061] Comparative Example 3:

[0062] The high temperature and high humidity resistant antistatic layer was prepared by using the same formula and steps as in Example 1, except that the amount of component C was 0 g.

[0063] Comparative Example 4:

[0064] The same formula and steps as those in Example 1 were used to prepare an antistatic layer resistant to high temperature and high humidity, except that γ-methacryloxypropyltrimethoxysilane was used instead of γ-glycidyloxypropyltrimethoxysilane.

[0065] Comparative Example 5:

[0066] The same formula and steps as those in Example 1 were used to prepare an antistatic layer resistant to high temperature and high humidity, except that the amount of component G was 10 g.

[0067] Comparative Example 6:

[0068] The high temperature and high humidity resistant antistatic layer was prepared by using the same formula and steps as in Example 1, except that isophorone diisocyanate was used instead of trimethylolpropane-tris[3-(2-methylaziridinyl)propionate].

[0069] After completing the preparation of the embodiments and comparative examples, the present invention tests the performance of the samples through experiments.

[0070] The experiments and steps are as follows:

[0071] 1. Initial antistatic properties

[0072] After the sample is coated and removed from the machine, select test points on the film surface and mark them on the back of the film with a marker. Use a resistance meter (model: Trek Model 152-1) to test the surface resistance of the sample. A test value of <1.0E+10Ω is considered qualified.

[0073] 2. Initial friction resistance

[0074] Fold the dust-free cloth twice and place it on the film surface at the corresponding test point. Press a 2kg weight on the dust-free cloth and drag the dust-free cloth with your hand to scrape. Repeat the scraping five times and then test the resistance value of the antistatic layer.

[0075] 3. Initial solvent resistance

[0076] 3.1 Fold the dust-free cloth twice and place it on the film surface at the corresponding test point. Drop 10ml of alcohol on the dust-free cloth, press a 2kg weight on the alcohol drop position of the dust-free cloth, drag the dust-free cloth with your hand to scrape, repeat the scraping 5 times, wait for the solvent to evaporate, and then test the resistance value of the antistatic layer.

[0077] 3.2 Fold the dust-free cloth twice and place it on the film surface at the corresponding test point. Drop 10ml of ethyl acetate on the dust-free cloth. Press a 2kg weight on the dust-free cloth where the ethyl acetate is dropped. Drag the dust-free cloth with your hand to scrape. Repeat the scraping 5 times. After the solvent evaporates, test the resistance value of the antistatic layer.

[0078] 4. Resistant to high temperature and high humidity

[0079] The samples were placed under 60°C / 90% RH and 85°C / 85% RH conditions for 7 days, and then left at room temperature for 12 hours before being tested according to 2. Abrasion resistance and 3. Solvent resistance.

[0080] The results are shown in Table 2

[0081] Table 2 Test results of various embodiments and comparative examples

[0082]

[0083]

[0084] From Table 2, the test results of Examples 1-3 and Comparative Examples 1-6 show that:

[0085] The antistatic properties, friction resistance, high temperature and high humidity aging resistance, and solvent resistance of Example 1 all meet the use requirements;

[0086] In Example 2, the amount of waterborne polyurethane and curing agent was increased, the dilution ratio was increased, the amount of methyl pyrrolidone was reduced, and the coating thickness was reduced to 0.05 μm. The surface resistance value decreased slightly, but the friction resistance, high temperature and high humidity aging resistance, and solvent resistance were improved, and still met the use requirements.

[0087] In Example 3, the amount of waterborne polyurethane resin and curing agent used was reduced, the dilution ratio was reduced, and the amount of methyl pyrrolidone was increased. The coating thickness was increased to 1 μm, which significantly reduced the surface resistance value. However, the initial friction resistance and solvent resistance after high temperature and high humidity were slightly reduced.

[0088] Compared with Example 1, in Comparative Example 1, the amount of waterborne polyurethane used was reduced to 100 g. There was no significant difference in the initial surface resistance value, but the friction resistance and solvent resistance were significantly reduced.

[0089] Compared with Example 1, Comparative Example 2 increases the amount of water-based polyurethane to 400 g, resulting in a significant increase in the initial surface resistance value, which cannot meet the use requirements, but there is no significant difference in friction resistance, solvent resistance, and high temperature and high humidity resistance.

[0090] Compared with Example 1, Comparative Example 3 reduces the amount of methyl pyrrolidone to 0g, resulting in a significant increase in the initial surface resistance value, and there is no obvious difference in friction resistance, solvent resistance, and high temperature and high humidity resistance. However, due to the high initial surface resistance, the resistance value after the friction resistance test and the solvent resistance test is at risk of exceeding the standard, which cannot meet the use requirements.

[0091] Compared with Example 1, Comparative Example 4 uses γ-methacryloxypropyltrimethoxysilane instead of γ-glycidyloxypropyltrimethoxysilane. There is no obvious difference in the initial surface resistance, but the high temperature and high humidity resistance is slightly reduced. After aging for 7D at 60℃ / 90%RH, the surface resistance shows a significant increase. After solvent resistance testing, the surface resistance exceeds the standard and cannot meet the use requirements.

[0092] Compared with Example 1, in Comparative Example 5, the amount of cross-linking agent was reduced to 10 g. There was no significant difference in the initial surface resistance, but the friction resistance and solvent resistance were significantly reduced initially and after high-temperature and high-humidity aging.

[0093] Compared with Example 1, Comparative Example 6 uses isophorone diisocyanate instead of trimethylolpropane-tris[3-(2-methylaziridinyl)propionate], and there is no significant difference in initial surface resistance, but the solvent resistance and high temperature and high humidity resistance are significantly reduced.

[0094] The above descriptions are merely optional embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the description of the present invention under the inventive concept of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A high temperature and high humidity resistant antistatic primer, characterized in that: These include the following substances: Component A: PEDOT / PSS antistatic liquid with a solid content of 1.5-2.5%; Component B: thermosetting waterborne polyurethane with a solid content of 33-38%; Component C: doping organic solvent; Component D: pH regulator; Component E: surfactant; Component F: silane coupling agent; Component G: a multifunctional aziridine crosslinker with a solid content of 9%-11%; Component H: a mixed solution of water and isopropyl alcohol.

2. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The mass of component B is 15-30% of the mass of component A, the mass of component C is 0.5-10% of the mass of component A, the mass of component D is 1-3% of the mass of component A, the mass of component E is 0.1-0.5% of the mass of component A, the mass of component F is 0.1-0.5% of the mass of component A, the mass of component G is 3-7% of the mass of component A, and the mass of component H is 9-15 times the mass of component A.

3. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The mass ratio of PEDOT to PSS in the PEDOT / PSS antistatic liquid is 1:2.5-1:

3.

4. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The thermosetting waterborne polyurethane is a thermosetting waterborne polyurethane containing hydroxyl groups and carboxyl groups.

5. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The doping organic solvent is a high-boiling-point polar solvent, including at least one of ethylene glycol, dimethyl sulfoxide (DMSO), sorbitol, and N-methylpyrrolidone.

6. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The pH regulator is an amine compound, specifically one of N,N-dimethylethanolamine, triethanolamine, and tert-butyldiethanolamine.

7. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The surfactant is a nonionic surfactant.

8. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The silane coupling agent is an epoxy silane coupling agent, specifically γ-glycidyloxypropyltrimethoxysilane.

9. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: The multifunctional aziridine crosslinking agent is a trifunctional aziridine, specifically one of trimethylolpropane-tris[3-(2-methylaziridinyl)propionate] and pentaerythritol tris(3-aziridinyl)propionate.

10. The high temperature and high humidity resistant antistatic primer according to claim 1, characterized in that: In the H component, the mass ratio of the water and isopropyl alcohol mixed solution is 1:1 to 1:2.

5.

11. A high temperature and high humidity resistant antistatic coating, characterized by: The antistatic coating is prepared using any one of the high temperature and high humidity resistant antistatic primers as claimed in claims 1 to 10, wherein the thickness of the antistatic coating is 0.05 to 0.1 μm.

12. A method for preparing a high temperature and high humidity resistant antistatic coating, for preparing the high temperature and high humidity resistant antistatic coating according to claim 11, characterized in that: The steps include: S1. Mix the water and isopropyl alcohol in component H and stir for 5 minutes, then let it stand for 5 minutes. Then, add components A, B, C, D, E, and F to component H in sequence and disperse them for 20-30 minutes. Finally, add component G and disperse for 5 minutes to obtain an antistatic primer. S2, coating the obtained antistatic primer on a PET substrate, controlling the dry coating thickness to be 0.05-0.1 μm, and curing at 120° C. for 1 minute to obtain a stable high-temperature and solvent-resistant antistatic layer.